Amyloid-beta (1-40) peptide is associated with systemic metabolic health - Sopova, Kateryna; Delialis, Dimitrios; Aivalioti, Evmorfia; Georgiopoulos, Georgios; Athanasopoulos, Stravros; Zervas, Georgios; Konstantaki, Christina; Sachse, Marco; Sigl, Martin; Dürschmied, Daniel; Tual-Chalot, Simon; Stamatelopoulos, Kimon; et al. (European journal of clinical investigation, 2026)
Background Amyloid-beta 1-40 peptide (Aβ40) has recently emerged as a blood-based biomarker of cardiovascular disease (CVD). However, whether plasma levels of Aβ40 are associated with metabolic traits in humans without established CVD remains poorly understood. Methods Aβ40 was measured in plasma by ELISA and metabolic traits (waist circumference, fasting triglycerides, fasting HDL cholesterol and fasting glucose) were determined in a general population (n = 449) of individuals who did not have clinically overt CVD. Triglyceride-glucose index (TyG) was used to calculate the risk for insulin resistance. BARD score was used to calculate the risk for metabolic liver disease. Results Aβ40 levels were associated with the presence of metabolic syndrome (OR: 1.41 95% CI: 1.13-1.76, p = .003), and with higher odds for increasing incidence of metabolic syndrome components, characterized by decreased HDL-C levels (OR: 1.31 95% CI: 1.03-1.58, p = .017) and increased triglyceride levels (OR: 1.30 95% CI: 1.04-1.57, p = .033) after adjustment for traditional cardiovascular risk factors. Further, Aβ40 levels were associated with increased odds for TyG (OR: 1.26 95% CI: 1.03-1.57, p = .042) and increased odds for the presence of diabetes mellitus (OR: 1.35 95% CI: 1.04-1.76, p = .018) after adjustment for age and sex, smoking status, hypertension and dyslipidemia. Increased Aβ40 levels were associated with increased odds for BARD score ≥2 (OR: 1.41 95% CI: 1.04-2.04, p = .045) after adjustment for traditional cardiovascular risk factors. Conclusion Our findings suggest that Aβ40 peptide is associated with metabolic traits and risk for metabolic disease. Future longitudinal studies are warranted to determine the prognostic value of Aβ40 for the development and progression of metabolic diseases.